Addressing the Challenges of Tuberculosis: A Brief Historical Account - Al-Humadi, Hussam W.; Al-Saigh, Rafal J.; Al-Humadi, Ahmed W. (Frontiers in Pharmacology, 2017)
Tuberculosis (TB) is a highly contagious disease that still poses a threat to human health. Mycobacterium tuberculosis (MTB), the pathogen responsible for TB, uses diverse ways in order to survive in a variety of host lesions and to subsequently evade immune surveillance; as a result, fighting TB and its associated multidrug resistance has been an ongoing challenge. The aim of this review article is to summarize the historical sequence of drug development and use in the fight against TB, with a particular emphasis on the decades between World War II and the dawn of the twenty first century (2000).